Clown in a cornfield [videorecording (DVD)] - Blanchard, Carter; Cesare, Adam; Craig, Eli, 1972-; Douglas, Katie; Abrams, Aaron, 1978-; MacCormac, Carson (Shudder, 2025)
Looking for a fresh start, Quinn and her father move to the quiet town of Kettle Springs. They soon learn the fractured community has fallen on hard times after losing a treasured factory to a fire.